A case of intraparenchymal occipital lobe Schwannoma in Shiraz, Southern Iran - Mousa Taghipour; Seyed Mohammad Rakei; Forouz Nader; Saeed Saadati (Journal of Research in Medical Sciences, 2008)
One case of intraparenchymal Schwannoma of right occipital lobe is presented (first report of occipital lobe Schwannoma). The radiological and pathological features of this rare tumor are discussed, and the current theories for etiology of these intraaxial nerve-sheath tumors are reviewed. KEY WORDS: Schwannoma, brain neoplasm, occipital lobe.